The Utilization of Mathematics Digital Learning Media: GeoGebra, Desmos, and Symbolab in Junior High School - Santri Chintia Purba; Verdinando Taek; Novi Suranti; Dimas Cristopel (Jurnal Pengabdian Sains dan Humaniora, 2026)
The primary issue encountered by the partner in this community service program is the lack digital learning media in mathematics instruction. At the junior high school level, particularly in Grade VII, students are undergoing a transition from concrete to abstract mathematical thinking, which necessitates the use of technology to help them visualize algebraic forms through graphs and various geometric representations of mathematical concepts. This community service program aims to enhance the quality of mathematics learning through the use of digital-based instructional media. The implementation consisted of several stages, namely school needs assessment, training on the use of digital applications, classroom mentoring by facilitators, and evaluation through questionnaires and interactive quizzes. The results of the program indicate that 161 students responded positively to digital-based mathematics learning. This is evidenced by the following findings: 93,16% of students reported enjoying the learning activities; 96,89% expressed interest in using GeoGebra, Desmos, and Symbolab; 93,16% stated that they understood how to use these applications; 83.85% agreed that the material presented was aligned with their learning needs at school; and 85,71% noted that the applications were easy to access. Thus, nearly all students experienced lessons that were engaging, enjoyable, and easy to understand. Keywords: digital learning, mathematics, Geogebra, Desmos, Symbolab